2020
DOI: 10.1002/agg2.20060
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on acidification of soils by nitrogen and sulfur fertilizers

Abstract: Some crops, like blueberries, require a pH of 4 to 5. Irrigation of acid‐loving crops with alkaline water can raise pH and cause micronutrient deficiencies. Diseases like citrus greening (Huanglongbing) are more severe at higher soil pH values. Application of acidifying fertilizers to lower soil pH may therefore benefit crop growth in such instances and release calcium from calcareous soils to remove sodium. Therefore, a good understanding of the processes involved and the amount of acidification from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Not many studies reported the impact of S fertilizers on SOC under oilseed crops; however, a study in Canada reported a 2–51% reduction in microbial biomass C with the application of elemental S fertilizer in grass field (Gupta et al, 1988). Studies have shown that the application of S fertilizer can increase soil acidity (Fageria et al, 2010; Kissel et al, 2020). However, in contrast, Wiedenfeld (2011) reported that an increase in salinity level was directly correlated with the increasing rate of S fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Not many studies reported the impact of S fertilizers on SOC under oilseed crops; however, a study in Canada reported a 2–51% reduction in microbial biomass C with the application of elemental S fertilizer in grass field (Gupta et al, 1988). Studies have shown that the application of S fertilizer can increase soil acidity (Fageria et al, 2010; Kissel et al, 2020). However, in contrast, Wiedenfeld (2011) reported that an increase in salinity level was directly correlated with the increasing rate of S fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Mencapai produksi yang optimal, tanaman vanili membutuhan pH dengan kisaran yang sedikit lebih rendah dari pH tanah di lokasi penelitian, yakni antara 5,5 hingga 6,5 (Hadipoentyanti et al, 2007;Ritung et al, 2011). Upaya penurunan pH tanah secara terkontrol dapat dilakukan melalui pemberian pupuk berbahan dasar nitrogen dan sulfat yang dapat mengasamkan tanah (Kissel et al, 2020).…”
Section: Reaksi Tanah (Ph)unclassified
“…Matos Castañon et al [36] concluded that soil pH was decreased linearly with increasing elemental sulfur doses. The optimal value of pH for the growth and development of many crops ranges from 6 to 7 [37]. It is assessed that acidic soils (characterized by topsoil pH < 5.5) cover nearly 30% and 50% of the world's total The optimal value of pH for the growth and development of many crops ranges from 6 to 7 [37].…”
Section: Soil Phkclmentioning
confidence: 99%
“…The optimal value of pH for the growth and development of many crops ranges from 6 to 7 [37]. It is assessed that acidic soils (characterized by topsoil pH < 5.5) cover nearly 30% and 50% of the world's total The optimal value of pH for the growth and development of many crops ranges from 6 to 7 [37]. It is assessed that acidic soils (characterized by topsoil pH < 5.5) cover nearly 30% and 50% of the world's total land and arable land area, respectively.…”
Section: Soil Phkclmentioning
confidence: 99%
See 1 more Smart Citation